2014
DOI: 10.1302/0301-620x.96b9.33755
|View full text |Cite
|
Sign up to set email alerts
|

Evertor muscle activity as a predictor of the mid-term outcome following treatment of the idiopathic and non-idiopathic clubfoot

Abstract: Previous studies have identified clinical and demographic risk factors for recurrence in the treatment of idiopathic clubfoot (congenital talipes equinovarus). Evertor muscle activity is not usually considered amongst them. This study aimed to evaluate whether recurrence could be predicted by demographic, clinical and gait parameters. From a series of 103 children with clubfeet, 67 had completed a follow-up of two years: 41 male and 26 female, 38 with idiopathic and 29 with non-idiopathic deformities. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 22 publications
1
38
0
2
Order By: Relevance
“…Edmonds and Frick [26] described the drop toe sign in nine [13] reported complex idiopathic deformity in 50 out of 762 clubfoot patients (6.5%). Poor evertor muscle activity was reported in 19 out of 59 idiopathic clubfeet (32.2%) following primary correction by Gelfer et al [29]. On the other hand, Chaudhry et al [22] using the Dimeglio score reported no case of positive MA parameter at presentation in their study, which we consider to be unlikely.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Edmonds and Frick [26] described the drop toe sign in nine [13] reported complex idiopathic deformity in 50 out of 762 clubfoot patients (6.5%). Poor evertor muscle activity was reported in 19 out of 59 idiopathic clubfeet (32.2%) following primary correction by Gelfer et al [29]. On the other hand, Chaudhry et al [22] using the Dimeglio score reported no case of positive MA parameter at presentation in their study, which we consider to be unlikely.…”
Section: Discussionmentioning
confidence: 54%
“…Muscular abnormalities are not uncommon in clubfeet [27][28][29] and a primary role of muscle impairment in the aetiopathogenesis of clubfoot has been suggested [30]. Several pathologic and clinical studies have shown in muscles of most clubfeet variably increased fibrous tissue (mainly in gastrosoleus, tibialis posterior and long toe flexor) [1,27] and atrophy, which is primitive and already present before starting treatment [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of this anomalous muscle may increase the likelihood of clubfoot being resistant to casting treatment [30]. Additionally, poor eversion muscle activity qualitatively assessed on physical exam has been demonstrated as a risk factor for relapse of clubfoot [31].…”
Section: Predicting Treatment Resistance and The Role Of Imagingmentioning
confidence: 99%